2022
DOI: 10.3389/fnano.2022.823236
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Microorganisms From the Tropics as Biofactories for the Synthesis of Metal-Based Nanoparticles: Healthcare Applications

Abstract: Nanoparticles (NPs) have gained great attention in recent years due to their extensive and innovative applications in the field of medicine. However, conventional physicochemical approaches for the synthesis of NPs may be limited and costly, and the reaction by-products are potentially toxic for human health and the environment. Bio-mediated synthesis of NPs exploiting microorganisms as nanofactories has emerged as an alternative to traditional methods, as it provides economic and environmental benefits. Tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…Bogas and their team have shown that these endophytes could act as biofactories for nanoparticles. NPs synthesized from such endophytes have immense potential in healthcare applications ( Bogas et al., 2022 ). In addition, Rathore and his colleagues have placed an emphasis on bacterial endophytes, discussing the recent biomedical scope of these organisms, as well as their synthesis, associated challenges, and importance in bio-nanotechnology ( Rathore et al., 2022 ).…”
Section: Role Of Endophytes In Bio-nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bogas and their team have shown that these endophytes could act as biofactories for nanoparticles. NPs synthesized from such endophytes have immense potential in healthcare applications ( Bogas et al., 2022 ). In addition, Rathore and his colleagues have placed an emphasis on bacterial endophytes, discussing the recent biomedical scope of these organisms, as well as their synthesis, associated challenges, and importance in bio-nanotechnology ( Rathore et al., 2022 ).…”
Section: Role Of Endophytes In Bio-nanotechnologymentioning
confidence: 99%
“… Schematic diagram representing steps involved in the anti-cancer activity of NPs synthesized by endophytes adopted from Bogas et al., ( Bogas et al., 2022 ). …”
Section: Role Of Endophytes In Bio-nanotechnologymentioning
confidence: 99%
“…Fungal and bacterial endophytes have been proposed as biofactories for the production of metal-based NPs with agricultural and therapeutic applications [10,29]. These microbes colonize plant intra-and/or intercellular tissues, forming a symbiotic connection [16,30].…”
Section: Biosynthesis Of Nanoparticles: Endophytic Microbiomes As Bio...mentioning
confidence: 99%
“…These processes can occur as either intracellular or extracellular events, and NPs synthesized by microorganisms are thus classed accordingly as either intra-or extracellular NPs [9]. Microorganisms have been used for the biosynthesis of the following NPs: Selenium, silver, tellurium, gold, silica, platinum, titania, uraninite, palladium, and quantum dots (QDs), zirconia, and magnetite nanoparticles [10]. Microorganisms are highly diverse, multiply rapidly, and are adaptable to a variety of environments, making them ideal systems for biological production processes, especially when compared to larger organisms, such as plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…All of this variety in generating groups makes bio-fabrication of metal-NPs using endophytes desirable. Because these groups can be used as effective reducing/capping agents in the synthesis of green NPs 20 . Myco-fabricated NPs are produced in a less expensive, safer, and non-toxic manner by employing endophytic fungus cells rather than other endophytes.…”
Section: Introductionmentioning
confidence: 99%